2012
DOI: 10.1021/ef201676t
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen in Biomass Char and Its Fate during Combustion: A Model Compound Approach

Abstract: The emission of nitrogen oxide (NO x ) from biomass combustion is still a concern, even though the nitrogen content of biomass in general is relatively small. To elucidate the pathways of fuel N conversion during combustion processes, many studies have focused on the pyrolysis of amino acids and/or model compounds. In contrast, the model compound char nitrogen and its fate during combustion have not been investigated. The partitioning of nitrogen between the volatiles and char and the type of nitrogen species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 34 publications
2
20
0
Order By: Relevance
“…Protein decomposition leads to the formation of volatile cyclic amides which, due to cracking reactions, produces HCN among other components [41]. The second peak stood out for the early apparition of NO 2 followed by the NO emission at higher temperatures for all samples except for W. These results agree well with those reported by Darvell et al (2012) [5] who found two stages for the combustion of different biomass char model samples. These stages were characterized by the release of NO at higher temperatures and the presence of sharper peaks.…”
Section: Evolved Gas Analysissupporting
confidence: 90%
See 1 more Smart Citation
“…Protein decomposition leads to the formation of volatile cyclic amides which, due to cracking reactions, produces HCN among other components [41]. The second peak stood out for the early apparition of NO 2 followed by the NO emission at higher temperatures for all samples except for W. These results agree well with those reported by Darvell et al (2012) [5] who found two stages for the combustion of different biomass char model samples. These stages were characterized by the release of NO at higher temperatures and the presence of sharper peaks.…”
Section: Evolved Gas Analysissupporting
confidence: 90%
“…In spite of the environmental advantages, some aspects concerning the release of contaminants during biomass combustion must be taken into account. In this regard, NO x and SO x emissions depend on raw biomass composition, which usually is variable [5]. The control of NO x and SO x from biomass combustion can contribute to decrease the emissions of these pollutants in Canada which are around 0.7 and 1.2 million tons per year for NO x (as NO 2 ) and SO 2 , respectively [6].…”
Section: Introductionmentioning
confidence: 99%
“…One stage was related to the release of amines and NO 2 , which was attributed to the decomposition of proteins (Darvell et al, 2012). In the second one, NO 2 was only detected and attributed to the oxidation of the retained N 2 in the char (Darvell et al, 2010).…”
Section: Combustionmentioning
confidence: 99%
“…In bituminous coal combustion, the heterocyclic N-compounds form mainly HCN, but in biomass, fuel-N can exist both as heterocyclic compounds and as amino acid groups in proteins. Hence, NO can be formed from the HCN intermediate produced from the heterocyclic compounds, while the protein nitrogen can be converted into both HCN and NH3 intermediates and ultimately NO together with some HNCO (Darvell et al, 2012;Hansen and Glarborg, 2010;Hansson et al, 2003aHansson et al, , 2003bRen et al, 2011;Stubenberger et al 2008). The protein nitrogen content of wood has been estimated to be in the range of 70-90 wt.% of the total nitrogen, and therefore a combination of both the HCN and NH 3 routes has to be considered.…”
Section: Introductionmentioning
confidence: 99%